Case of adenohypophysis adenocarcinoma according to postmortem results - N. Yu. Ozerova (Zaporozhye State Medical University, 2012)
This article describes a case of rare disease - adenocarcinoma of adenohypophysis. A tumour had extremely small size and was accompanied by destruction of wall of the sella turcica and invasion of blood vessels, that resulted in development of thrombosis of right cavernous sinus with typical clinical features. Described case is of interest for physicians as diagnostics and therapy of this disease are extremely difficult.